Survey on Sentimental Analysis and Visualization of Reviews - Chugh, Bhanu; Arya, Sejal; Pandita, Mayank; Jain, Tanmay; Bhole, GV (International Journal of Computer Sciences and Engineering, 2020)
The time when the food ordering websites are filled with tons of review data regarding the quality and quantity of food. One can extract tons of conclusions while analyzing it. In this survey paper, we will study various techniques to analyze the data including algorithms like Naive Baye’s, SVM, etc. and their outcomes in the field of data mining and sentimental analysis. Sentimental analysis is a boon for the restaurant owners as they can restructure their unique selling points and services. Customers can indeed use the data to filter the restaurants according to the area, cuisines, dining time, etc. to make an opinion. Also, in the end, polarising the high-quality dataset into positive and negative vows to visualize it for the customers. Tableau the most majestic tool can help us to do the same. Working on emoticons as well as text will take us to a hard way to complete the study.